Opposite evolution on voltage and thickness from paroxysmal to persistent AF. (3rd October 2022) - Silva Garcia, E; Banez, V; Gonzalez, M; Puche, J E; Gomez, A; Cano, L; Fernandez, R; Fernandez, M; Fernandez-Armenta, J
Abstract: Background: There is a controversy about correlation between voltage and thickness in the atrial myocardium and their evolution from paroxysmal to persistent atrial fibrillation (AF). Purpose: This is an observational study to compare voltage and thickness of different areas on the left atrium in paroxysmal and persistent atrial fibrillation. Methods: Twenty-one patients underwent atrial fibrillation ablation. Points with electrical information from an electroanatiomical map in sinus rhythym were acquiered during the ablation procedure covering the whole atrial surface. CT was acquired in all patients before the procedure and endo- and epicardium from the atrium was segmented for the atrial thickness calculation. All the points from the electromecanical map were projected on the thickness map to have both information on the same location. 3D atrium was segmented in 5 areas for the analysis: Lateral, Anterior, Septal, Inferior-Posterior and Superior-Posterior (Figure 1). Voltage and thickness values among different areas and between AF type were compared. Results: 11 paroxysmal and 10 persistent AF patients were analyzed acquiring 452±207 points per patient and 1897±750 points per area. There was no linear correlation between voltage and thickness comparing all the patients nor among different areas nor between AF type (R<0.2 in all cases). Regarding paroxysmal AF patients, septum showed significatly lower voltage compared with the other segments, posterior, lateral, anterior and roof (1.3±1.4, 2±1.8, 2±1.6, 1.7±1.5, 2±1.6, P<0.001). Posterior segment showed the highest voltage. The thickness analysis showed the septum segment as thinner segment and lateral as thicker segment (1.3±1.5, 1.7±0.8, P<0.001) (Figure 2). Regarding persisten AF patients: septum showed significatly lower voltage compared with the other segments, posterior, lateral, anterior and roof who shows higher voltage (1±0.8*, 1.5±1.2, 1.9±1.7, 1.5±1.4, 2±1.6) (Figure 2). The thickness analysis showed the anterior segment as thinner segment and lateral as the thickest segment (1.6±0.8, 1.9±0.9 (P<0.001), different like on paroxysmal AF population. Comparing voltage and thicknes between paroxysmal and persistent AF, all the segments on persistent population showed lower voltage values, with significant differences on septal, posterior and anterior walls (1±0.8 vs 1.3±1.4, 1.5±1.2 vs 2±1.8, 1.5±1.4 vs 1.7±1.5, P<0.001). On the other hand, all segments on persistent population showed statisticaly signignificant thicker myocardium in camparison with paroxysmal population (Figure 2). Conclusions: According to our findings, there is no linear correlation between voltage and thickness. Persistent AF atria show thicker walls but with lower voltages in comparison with paroxysmal AF atria. Funding Acknowledgement: Type of funding sources: None.